INTERNATIONALIZATION STRATEGIES OF EMERGING COMPANIES: A COMPARATIVE STUDY OF BRAZILIAN CASES - Bueno, Janaína Maria; Domingues, Carlos Roberto (Future Studies Research Journal: Trends and Strategies, 2012)
Over the last decade, interest has picked up as to emerging economies and their companies. This recent movement does not imply that previous theories and models are no longer applicable, however, one must analyze, in a broader comprehensive manner, a series of specific context factors and those concerning the management of this kind of company. Therefore, this paper analyzed the internationalization strategies adopted by six Brazilian companies before a set of internationalization models. A qualitative research approach was employed and in-depth interviews were conducted with corporate management level professionals. Companies were divided into three groups according to internationalization times (Group I – over ten years, Group II - between five and ten years, and Group III – under five years). Observations indicated that for Groups I and III companies the product lifecycle (Vernon, 1966 and 1979) and the eclectic paradigm (Dunning, 1980, 1988 and 2000) economic models support justifying internationalization motivations for companies’ internalization whilst the Uppsala model (Johanson and VAHLNE, 1979, 2009), at least in part explains, choice decisions concerning a few countries. As to Group II companies, the product lifecycle model is not the underlying motivation for internationalization, choices being more closely related to sector opportunities and the characteristics of both products and services.